Cardiovascular health assessed using Life’s Essential 8 is associated with all-cause and cardiovascular disease mortality among community-dwelling older men and women in the InCHIANTI study - Vivek Sarma; Yichen Jin; Stefania Bandinelli; Sameera A. Talegawkar; Luigi Ferrucci; Toshiko Tanaka (Frontiers in Public Health)
IntroductionThe older population is growing fast, and it is important to investigate the cardiovascular health factors and behaviors that are associated with cardiovascular disease (CVD) and mortality among older individuals.MethodsA total of 920 older adults (mean age: 74 years, 55% women) from the InCHIANTI study were included for analysis. Cardiovascular health (CVH) was assessed using the Life’s Essential 8 (LE8) developed by the American Heart Association, including 8 health behaviors (smoking, diet, physical activity, sleep) and factors (body mass index, blood cholesterol, blood glucose, blood pressure). The LE8 score ranges from 0 to 100, with higher score indicating better CVH. CVH was analyzed on both a continuous scale [per 1 standard deviation (SD) increase] and categorical scale [low (CVH) score < 50 vs. moderate/high (CVH) score ≥ 50]. Cox hazard models were used to calculate the hazard ratios (HRs) of CVD and all-cause mortality associated with CVH and its components adjusting for age, sex, study site, education, presence of ADL and IADL limitations, cognitive impairment, depression, and presence of chronic disease.ResultsThe median follow-up time was 14.5 years. Participants with moderate/high CVH had better survival rates for both CVD and all-cause mortality compared to those with low CVH. One SD increase in LE8 score was associated with 28% (p = 0.001) and 17% (p < 0.001) lower risk of CVD and all-cause mortality, respectively.DiscussionAmong older community dwelling men and women, better CVH is inversely associated with CVD and all-cause mortality, and this lends credence to the importance of prioritizing health factors and behaviors in preventing chronic disease and promoting healthier lives among older adults.